Network analysis used to investigate the symptoms of cancer patients during chemotherapy: a scoping review - Xiaodan Shao; Na Wang; Ke Tang; Kunning Wang; Zhangyan Tan; Jiangxiu Xie; Zhiwei Shen; Yuting Jiang; Yan Zhang (Discover Oncology)
Abstract Objective To provide an overview of the symptom experience and interrelationships among symptoms during chemotherapy in cancer patients, as well as the state of symptom network research in this field. Methods This scoping review was conducted using the framework proposed by Arksey and O’Malley and the PRISMA guidelines. It included studies that focused on symptom network analysis of cancer patients currently undergoing chemotherapy treatment. A comprehensive search was conducted in both English and Chinese databases, including PubMed/MEDLINE, Cochrane, EMBASE, CINAHL (EBSCO), Web of Science, ProQuest, CNKI, VIPC, and CSPD, up to September 10, 2024.Studies were included if they involved cancer patients aged ≥ 18 years undergoing chemotherapy and excluded those involving radiotherapy. Data were extracted based on study characteristics, cancer types, sample characteristics, treatment, study design, instruments, R packages used, core symptoms, and main findings. Results From 8948 initial articles, 12 studies were included. These studies varied in sample size, symptom survey instruments, and methods of symptom categorization. Six studies extracted symptom clusters, and core symptoms were identified in eight studies. Fatigue was commonly reported as a core symptom across different cancer types. The longitudinal study indicated that overall symptoms peaked after the initial chemotherapy session and gradually decreased with subsequent cycles, although some symptoms like skin changes and neuropathy worsened over time. Conclusions Symptom network analysis offers insights into the complex interplay of symptoms during chemotherapy, highlighting fatigue as a central symptom. Future research should focus on longitudinal studies to better understand the dynamic changes in symptom networks and their implications for symptom management interventions.